The Mechanism of State-Public Management of Vocational Education in the Region - Pugacheva, Natalya B.; Kirillova, Tatiana V.; Ovchinnikova, Iraida G.; Kudyashev, Nail K.; Lunev, Alexander N.; Pavlova, Oksana A.; Kashina, Svetlana G.; Valeyev, Azat S. (International Review of Management and Marketing, 2016)
The relevance of the article is reasoned by the development of civil society and the positioning of vocational education as an open, state-public system. The purpose of the article is to develop a mechanism of state-public management of vocational education in the region. The leading method is the method of action research (AR), allowing obtain new knowledge about state-public management of vocational education in the region and to organize the systematic monitoring of the changes in state-society relations in the management of vocational education. The article reveals the essence and defines the principles of state-public management of vocational education in the region; presents a mechanism of state-public management of vocational education in the region, providing a constructive dialogue between the entities of management process and the formation of a unified regional educational environment. Article Submissions may be useful for research and teaching staff of the system of vocational education, specialists of education management bodies and regional authorities. Keywords: Vocational Education, State-Public Management, Social Partnership, Educational Institutions. JEL Classifications: A12, A20, H52, I23